2016
DOI: 10.2147/cia.s106284
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor gastrointestinal disorders in older patients with Parkinson’s disease: is there hope?

Abstract: Despite the fact that nonmotor symptoms (NMS) like gastrointestinal (GI) complaints are frequently reported in Parkinson’s disease (PD), no therapeutic guidelines are available. This study aimed to manage some lower GI-NMS in a group of patients with PD. A total of 40 patients (17 males, 23 females; mean age 76.05±2.09 years) were randomly selected for this study. Patients were confirmed to have PD (modified Hoehn–Yars scale: 2.075±0.4) who had undergone levodopa or dopamine agonist treatment. In the non-motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
95
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 25 publications
2
95
0
3
Order By: Relevance
“…Despite characterized by motor issues such as tremor at rest, rigidity, bradykinesia, PD also carries various types of NMS, [ 39 , 40 ] which are a supplementary burden and are often very difficult to manage satisfactorily. [ 41 ] Reports have examined the relations between UA levels and cognition in PD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Despite characterized by motor issues such as tremor at rest, rigidity, bradykinesia, PD also carries various types of NMS, [ 39 , 40 ] which are a supplementary burden and are often very difficult to manage satisfactorily. [ 41 ] Reports have examined the relations between UA levels and cognition in PD patients.…”
Section: Resultsmentioning
confidence: 99%
“…These results are paralleled with PD human studies showing the positive effects in MDS-UPDRS scores of PD patients after a 12-week administration of probiotics [29], encouraging further research into its therapeutic application. Other human studies have also shown several beneficial effects of probiotics in PD, including the alleviation of the symptoms in abdominal pain, bloating, and constipation and the improvements in stool consistency and defecation habits [28,48,49]. It has been increasingly reported that the gut microbial dysbiosis and alteration of microbial metabolites could play a role in the pathogenesis of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Non-motor manifestations, which precede the motor disabilities in PD patients, play a key role in the disease progression and evidence for their significance has gradually accumulated [24]. Among the non-motor symptoms of PD, gastrointestinal (GI) dysfunction, including drooling, impaired gastric emptying, and constipation are frequently reported [5, 6].…”
Section: Introductionmentioning
confidence: 99%